Effect of Extracts, Fractions, and Isolated Molecules of Casearia sylvestris to Control Streptococcus mutans Cariogenic Biofilm - Ribeiro, Sabrina M. [UNESP] (2023)
The effects of extracts, fractions, and molecules of Casearia sylvestris to control the cariogenic biofilm of Streptococcus mutans were evaluated. First, the antimicrobial and antibiofilm (initial and pre-formed biofilms) in prolonged exposure (24 h) models were investigated. Second, formulations (with and without fluoride) were assessed for topical effects (brief exposure) on biofilms. Third, selected treatments were evaluated via bacterium growth inhibition curves associated with gene expression and scanning electron microscopy. In initial biofilms, the ethyl acetate (AcOEt) and ethanolic (EtOH) fractions from Brasília (BRA/DF; 250 µg/mL) and Presidente Venceslau/SP (Water/EtOH 60:40 and Water/EtOH 40:60; 500 µg/mL) reduced ≥6-logs vs. vehicle. Only the molecule Caseargrewiin F (CsF; 125 µg/mL) reduced the viable cell count of pre-formed biofilms (5 logs vs. vehicle). For topical effects, no formulation affected biofilm components. For the growth inhibition assay, CsF yielded a constant recovery of surviving cells (≅3.5 logs) until 24 h (i.e., bacteriostatic), and AcOEt_BRA/DF caused progressive cell death, without cells at 24 h (i.e., bactericidal). CsF and AcOEt_BRA/DF damaged S. mutans cells and influenced the expression of virulence genes. Thus, an effect against biofilms occurred after prolonged exposure due to the bacteriostatic and/or bactericidal capacity of a fraction and a molecule from C. sylvestris.